Programy Unii Europejskiej jako źródło finansowania turystyki uzdrowiskowej w Polsce - Żylak, Danuta; Hadzik, Andrzej (European Union's Structural Funds as Possibilities Financing Development of Tourism Health Resort in Poland, 2005)
Health tourism is a voluntarily going for some time out of place of living for vitality regeneration through active rest both physical as psychical. In polish health tourism functions: therapeutic and touristic are cleary seen and should not be competitive. Improvement of infrastructure in health tourism is the big chance of development as well as in services like "public health" or fitness, wellness, beauty and SPA. The branch of health tourism, tourism and recreation and health services have one of very important potentials of development. This is connected with creation of new working places. That is why Structural Funds of EU are the big possibility for polish tourism.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1074, s. 181-188